Implementation of the Ulul Ilmi Model in PAI Learning to Improve Student Character - Nurti Budiyanti; Aan Hasanah; Muhibbin Syah; Andewi Suhartini (Perhimpunan Intelektual Muslim Indonesia, 2023)
The decline in the quality of education in Indonesia is inseparable from the decline in quality possessed by educators, especially the shift in the educational paradigm often appears as one of the consequences of the mixing of Western paradigms that enter the world of education, so that the learning process is directed to the success of the logical and empirical thought process. While in the Islamic paradigm, the learning process is directed to think logically, empirically and theologically. This is related to the way the development of quranic learning models carried out by an educator in the classroom. The Ulul Ilmi model has an output to produce student characters that have the character of Ulul Ilmi. This paper aims to implement the Ulul Ilmi model in PAI learning to improve the character of students, which can certainly help realize national education goals. The research methodology used by the author uses a qualitative approach. Research data is taken from the learning process carried out by UPI students through observation, interview, and documentation. The data was then analyzed using Miles and Huberman's theory. Based on the results of the study, the Ulul Ilmi model in PAI learning is implemented following ten learning syntactic using a scientific approach contained in the initial, core and final activities. This model has an impact on improving the quality of educator performance and the quality of the learning process that is more valuable to deliver to the output of the learning process so that the character of Ulul Ilmi is formed. In addition, in its implementation the learning process needs careful readiness that needs to be considered by educators and learners, be it physical readiness, psychic, adequate equipment and learning facilities in order to minimize various inhibitory factors that occur during the implementation of the Ulul Ilmi model in the PAI learning process, because with careful preparedness, the learning process runs in accordance with the learning syntapositions that have been formulated in order to achieving the expected results, in forming the character of students in order to have the character of Ulul Ilmi.